Clinical findings in patients with leprosy who are infected with COVID-19: a case series from Elazig, Turkey - Dertlioglu, Selma Bakar; Karlidag, Gulden Eser; Aglamis, Serpil (Lepra, 2021)
Background: Leprosy is a chronic granulomatous infectious disease caused by Mycobacterium leprae that can be self-limiting or progressive according to the immunological status of the host organism. Aim and objectives: We present the demographic and clinical characteristics of lepromatous leprosy (LL) patients who had Covid-19 infection. Materials and methods: This study recruited patients hospitalized in Elazig Leprosy Hospital. Details of the patients were collected as follows: age, gender, presence of comorbidity, leprosy classification, clinical presentation, presence of leprosy reactions and complaints at the time of admission; laboratory and computed tomography (CT) findings and treatments applied. Results: This study included 9 patients with lepromatous leprosy (LL classification). Six patients were PCR positive for SARS-CoV-2, 7 patients had thoracic CT involvement. The mean age was 78.7 years (range 65-95). Complaints on admission included fatigue (n:7), cough (n:4) and fever (n:3) followed by sore throat (n:1), headache (n:1) and dysphonia (n:1). Two patients were asymptomatic, PCR positivity was detected in one and CT positivity was detected in another during screening. All patients received treatment with favipiravir and enoxaparin. No leprosy reactions occurred. All patients were discharged with recovery after completion of treatment. Conclusion: We expected that the risk for catching COVID-19 may be higher in LL patients who have a cellular immunity deficiency, and that the course of the infection may be more severe in COVID-19-infected LL patients, for the same reason. However, we have seen a decrease in the clinical severity of the COVID-19 and no patient losses. We conclude that this situation may be due to the drugs used for leprosy treatment.These immune-modulating drugs may cause a decrease in the clinical severity of the COVID-19, but we need larger studies on this subject.
Keywords: COVID-19; leprosy; cytokines; comorbidity; hypocalcemia